The burden of influenza and the role of influenza vaccination in adults aged 50-64 years: A summary of available evidence - Serena Marchi; Elettra Fallani; Marco Salvatore; Emanuele Montomoli; Claudia Maria Trombetta (Taylor & Francis Group, 2023)
Influenza is a vaccine-preventable disease and a global public health problem. Although most national influenza vaccination recommendations focus on subjects aged ≥65 years, an extensive burden of influenza has also been reported in those aged ≥50 years and is exacerbated by immune system aging. The main purpose of this review is to provide an overview of the burden of influenza and its potential prevention within the 50-64 age-group. These subjects account for a large proportion of the workforce, and play a central economic and social role. Individuals aged 50-64 years had a 3-times higher rate of hospitalization and a 9-fold higher mortality rate attributable to influenza than those aged 18-49-years, generating higher influenza-related hospitalization costs. Available data suggest that including healthy subjects aged 50-64 years in influenza vaccination recommendations would allow a broader population to be reached, reducing the economic and social burden of influenza.